Constraining models with superlight gravitino, scalar and pseudoscalar particles - Mori, F.; Natale, A. A. [UNESP] (World Scientific Publishing, 2000)
In some supergravity models there are light weakly coupled scalar (S)-and pseudoscalar (P) particles. These particles arise following a superlight gravitino. In these models the decay SIP → γγ exists. We examine constraints on this process considering these photons as responsible by the extragalactic background light. We also consider the amount of SIP particles produced through the fusion of the cosmic background photons and contributing to the effective number of light neutrino species during primordial nucleosynthesis. We obtain bounds on the gravitino mass complementary to the existing ones.
Keywords: gravity; light; mathematical analysis; model; photon; physics; temperature